PELATIHAN DAN PENDAMPINGAN PEMBUATAN SOCIAL MEDIA MARKETING UNTUK MENINGKATKAN KEMAMPUAN PROMOSI DAN OMSET PENJUALAN (Bagi Pelaku Bisnis UMKM Sektor Fashion Di Kota Denpasar) - Ni Nyoman Kerti Yasa; I Made Wardana; I Gusti Ayu Dewi Adnyani; Gede Bayu Rahantha; Putu Laksmita Dewi Rahmayanti; Ni Luh Wayan Sayang Telagawathi; Ni Putu Dyah Krismawintari (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2022)
MSMEs engaged in the fashion sector in the last two years have faced such intense competition. This is because there are more and more players in the MSME industry in the fashion sector in Denpasar City. This has an impact on the achievement of declining sales turnover. One way to overcome this condition is to do social media marketing (Social media marketing). Based on the results of initial interviews with ten SMEs in the fashion sector, information was obtained about the decline in sales turnover and the solution was that they had done social media marketing. Only social media marketing that has been done has not been maximized, that is, it has not shown high intensity by using all existing social media platforms. This is due to their limitations in using social media. This condition encourages this community service activity to be carried out to equip MSME businessmen in the fashion sector in Denpasar City about the importance of marketing products digitally, one of which is using social media optimally using all existing social media platforms, following trends in consumer behavior in seeking information, and about designing its advertising content. The purpose of this community service is to equip MSME actors in the fashion sector in Denpasar City about the importance of social media marketing, getting to know various existing social media platforms, designing advertising content on social media, and assisting in making social media comprehensively including creating Facebook, Instagram, Line accounts, Tik Tok, WhatsApp, in order to increase its promotional capabilities and sales turnover.